STRATEGI PENGHIMPUNAN DAN PENYALURAN DANA PADA BAITUL MAL WAT TAMWIL - SANWANI SANWANI; TITIEK HERWANTI; AKHMAD JUFRI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2017)
The theme of the article is the banks and financial institutions. The research objective was to determine strategies in collecting and distributing funds on BMT Al-Hidayah. The study was qualitative. Research technique is triangulation. The focus of the study was to determine the strategy that is used in collecting and distributing funds. Results of the study are: the collection and distribution of funds strategies used are: 1) Direct the place of prospective customers, 2) Social Care, 3) Marketing, and 4) Spread the brochure.